Archaeology of a Rural Landscape: The Case of the Tana Delta in Kenya - (:unkn) unknown (My University, 2019)
Since the 1940s, the history of coastal Kenya relies essentially on monumental trading centres studies of the last millennium and a half. On the contrary, hinterlands of those remarkable cities were not subjects of research before the late 1970s. During the 1980s two Kenyan archaeologists wrote their PhD thesis on coastal hinterlands, highlighting the interactions with the cities. G.O. Abungu proposed several trade network models between the Upper Tana River and the mouth of the same river, based mostly on similar decorated potteries. However, he did not take into account the deltaic area of the Tana River sufficiently, though he suggested its role of hinterland for Swahili cities. Therefore, my PhD aims to elaborate a history of this region based on the archaeological finds for the last 2 000 years. The study aims to shed light on the rural dynamics and the organisation of the past populations who inhabited the Tana Delta during this time scale. As such, I would like to interrogate the models proposed by my predecessors, based on archaeological and historical material. For this purpose, I try to understand the way people occupied and managed their environment, determining the subsistence and handcraft activities involved into a micro and macro scales, namely the site or village and the Delta. In a broader context, the Tana Delta can be analysed in a global scale: African inland and Indian Ocean trade networks.
Keywords: African Research